Characteristics and Clinical Outcomes in Patients With Heart Failure With Preserved Ejection Fraction Compared to Heart Failure With Reduced Ejection Fraction: Insights From the VCOR Heart Failure Snapshot - Tan, C.; Dinh, D.; Brennan, A.; Hare, D.L.; Kaye, D.; Lefkovits, J.; Lockwood, S.; Neil, C.; Prior, D.; Nasis, A.; Wilson, A.; Reid, Christopher; et al. (ELSEVIER SCIENCE INC, 2022)
Background: Heart failure is increasing in prevalence, creating a greater public health and economic burden on our health care system. With a rising proportion of hospitalisations for heart failure with preserved ejection fraction (HFpEF) compared to heart failure with reduced ejection fraction (HFrEF) and lack of proven therapies for HFpEF, patient characterisation and defining clinical outcomes are important in determining optimal management of heart failure patients. There is scarce Australian-specific data with regards to the burden of disease of patients with HFpEF which further limits our ability to appropriately manage this syndrome. Aim: To determine the characteristics, management practices and outcomes of patients with HFpEF compared to patients diagnosed with HFrEF. Method: Data was sourced from the Victorian Cardiac Outcomes Registry-Heart Failure (VCOR-HF) snapshot of patients admitted with acute heart failure to one of 16 Victorian health services between 2014–2017 over one consecutive month annually. Outcomes measured were in-hospital mortality, and 30-day readmission and mortality. Results: Of the 1,132 HF patients, 436 patients were diagnosed with HFpEF and were more likely to be female (59%) and older (81.5±9.8 vs 73.2±14.5 years). They were also more likely to have hypertension (80%), atrial fibrillation (59.9%), chronic obstructive airways disease (36.2%) and chronic kidney disease (68.8%). Patients with HFrEF were more likely to have ischaemic heart disease with a history of previous myocardial infarction (36.6%), percutaneous coronary intervention and cardiac bypass surgery (35.2%). There were no significant differences in 30-day mortality between HFpEF and HFrEF (10.2% vs 7.8%; p=0.19, respectively) and 30-day readmission rates (22.1% vs 25.9%; p=0.15, respectively). Conclusion: VCOR-HF Snapshot data provides important insight into the burden of acute heart failure. Whilst patients with HFpEF and HFrEF have differing clinical profiles, morbidity, mortality and re-admission rates are similar.